ANTIMICROBIAL ACTIVITY OF GYMNOSPERMA GLUTINOSUM (SPRENG.) LESS. (ASTERACEAE) METHANOL EXTRACTS AGAINST HELICOBACTER PYLORI - Gomez-Flores, Ricardo; Espinosa-Ramos, David; Quintanilla-Licea, Ramiro; Barrón- Gonzalez, MarÃa Porfiria; Tamez-Guerra, Patricia; Tamez-Guerra, Reyes; Rodriguez-Padilla, Cristina (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Prolonged use of antibiotics may lead to the selection of drug-resistant bacteria; as a result, efforts are being made to identify new and effective antimicrobial agents, particularly, from medicinal plants, against bacterial infections. Antimicrobial activity of Gymnosperma glutinosum against Helicobacter pylori has not yet been reported. Materials and methods: The antibacterial in vitro effect of Gymnosperma glutinosum methanol leaf extracts against Helicobacter pylori (ATCC 43504) was evaluated in liquid medium by the colorimetric 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) reduction assay and in solid medium by the colony forming units (CFU) method. Results: Methanol extracts significantly (p<0.05) inhibited in vitro H. pylori growth in liquid medium from 24% to 82% at concentrations ranging from 31.25 mg/ml to 500 mg/ml, respectively, and in solid medium the extracts caused significant (p<0.05) 52% and 100% bacterial growth inhibition at concentrations of 250 g/mL and 500 g/mL, respectively, as compared with untreated control. Methanol vehicle did not affect H. pylori growth. Conclusion: The observed antibacterial effect of G. glutinosum extracts may be of benefit as an adjuvant treatment of diseases caused by H. pylori.